3D evaluation of maxillary sinus in gender determination: A cone beam computed tomography study - Anju Mathew; Lisa Elizabeth Jacob (Wolters Kluwer Medknow Publications, 2020)
Background: Gender determination is a subdivision of forensic medicine and very crucial especially when information relating to the deceased is unattainable. Maxillary sinus remains intact even when the skull and other bones may be badly disfigured. Aim and Objectives: This study aimed at assessing the reliability of morphometric measurements performed on the maxillary sinus for gender determination by Cone Beam Computed Tomography. Materials and Methodology: The present study was conducted in the Department of Oral Medicine and Radiology to assess maxillary sinus dimensions of 100 patients with 200 sinuses [left and right maxillary sinuses] by Cone Beam Computed Tomography. Two independent observers measured the maxillary sinus parameters such as width, length, height, intermaxillary distance, bizygomatic distance in axial and coronal view. Discriminative analysis was performed using the derived values and independent t-test was used to compare the values between males and females. Results: The overall values of the maxillary sinus dimensions were significantly greater (p < 0.05) in males as compared to females except intermaxillary distance (p > 0.05). There was no significant difference while comparing the right and left side within the same gender (p > 0.05). Maxillary sinus height was a better discriminant parameter for sexual dimorphism with 80% accuracy. Conclusion: Maxillary sinus can be used as an aid in forensic anthropology for gender determination. CBCT measurement of Maxillary Sinus can be used as supplementary tool for gender determination.